2011
DOI: 10.2215/cjn.06970711
|View full text |Cite
|
Sign up to set email alerts
|

Sympathetic Nerve Traffic and Asymmetric Dimethylarginine in Chronic Kidney Disease

Abstract: SummaryBackground and objectives Sympathetic overactivity and high levels of the endogenous inhibitor of NO synthase asymmetric dimethylarginine (ADMA) are prevalent risk factors in chronic kidney disease (CKD).Design, setting, participants, & measurements In 48 stage 2 to 4 CKD patients, we investigated the relationship between efferent postganglionic muscle sympathetic nerve traffic (microneurography) and circulating ADMA and analyzed the links between these risk factors and estimated GFR (eGFR), proteinuria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 37 publications
(46 reference statements)
0
39
0
Order By: Relevance
“…Indeed, in stage 2-4 CKD patients, Grassi et al [55] demonstrated a strong negative association between increased muscle SNA and decreased GFR, as well as a significant positive correlation between high muscle SNA and proteinuria. Interstitial fibrosis, glomerulosclerosis [56], accelerated atherosclerosis, vasoconstriction, and proliferation of smooth muscle cells and adventitial fibroblasts in the vessel wall are other deleterious consequences of sympathetic overactivity related to progression of renal damage [57,58].…”
Section: Altered Autonomic Control Of Cardiovascular Function In Ckdmentioning
confidence: 98%
“…Indeed, in stage 2-4 CKD patients, Grassi et al [55] demonstrated a strong negative association between increased muscle SNA and decreased GFR, as well as a significant positive correlation between high muscle SNA and proteinuria. Interstitial fibrosis, glomerulosclerosis [56], accelerated atherosclerosis, vasoconstriction, and proliferation of smooth muscle cells and adventitial fibroblasts in the vessel wall are other deleterious consequences of sympathetic overactivity related to progression of renal damage [57,58].…”
Section: Altered Autonomic Control Of Cardiovascular Function In Ckdmentioning
confidence: 98%
“…Besides extrarenal effects, sympathetic overactivity influences renal sodium excretion and reabsorption, renal perfusion, glomerular filtration rate, and renin release [9,10]. Moreover, increased activity of the sympathetic nervous system is associated with estimated glomerular filtration rate (eGFR) and proteinuria suggesting that the activation of this system is a progression factor in CKD patients [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary hypertension in CKD-5 or ESRD on HD may be induced or aggravated by left ventricular dysfunction, volume overload [16][17][18], an arterial-venous istula [7,11,[19][20][21][22][23], sleep disorders [24][25][26][27][28][29][30], exposure to dialysis membranes [31], endothelial dysfunction [32], vascular calci ication and stiffness, and severe anemia. Controlling volume overload and left ventricular disorders are important for relieving PH.…”
Section: Hepatopulmonary Syndrome (Hps)mentioning
confidence: 99%